Effects of Beaver Dams on Subarctic Wetland Runoff - Waadington, James M. (My University, 1989)
Beaver dams located on streams of a western James Bay marsh were studied to determine their effects on the runoff from subarctic wetlands. A survey of the location, type, class, and geometry of 50 dams on five different creeks were related to streamflow hydrographs from 1987 field season. The hydrographs showed that although gapflow and overflow type dams stored more water upstream during low flow, little alteration to stormflow occurred except for the shedding of water to the surrounding wetland. Throughflow type dams altered streamflow only at the local scale, while underflow type beaver dams, despite having little affect at low flow, created a 12 hour time lag and a long hydrograph recession during high flows.
A water balance comparison was performed for the period June 18th to July 28th, 1988 between a basin without a beaver dam and one dammed by the beaver to determine the effects of the beaver dams at the basin scale. The amount of water stored in the beaver dam basin (18mm) was 53mm greater than that stored in the basin without a dam (-35mm) indicating a distinct difference in the basins' abilities to store water. In both basins, net subsurface flow was negligible. Precipitation was similar in magnitude between the two basins. Net surfaceflow in the beaver dam basin was 43mm compared to -28mm in the beaver dam-less basin. The beaver dam was responsible for preventing a portion of inflow from leaving the basin, and consequently caused the increase in storage. Increased evaporation occurred because of the larger ponded area upstream from the beaver dam which in turn decreased the amount of water stored in the basin. Downstream streamflow ceased during dry periods because of the loss and storage of water from the system upstream.
Title: Effects of Beaver Dams on Subarctic Wetland Runoff, Author: James M. Waddington, Location: Thode